Solar-based hybrid electric vehicles for low CO2 emission - Md. Ariful Islam; Pankaj Chandra Kar; Shamim Ahmed Deowan (International Journal of Sustainable Engineering)
This study investigates the impact of greenhouse gas and [Formula: see text] emissions from conventional vehicles (CVS) in Bangladesh and proposes a renewable energy and battery storage-based hybrid electric vehicle (HEV) to mitigate these emissions. The proposed HEV focuses on fuel economy, driving range, performance and cost-efficiency. It integrates hybrid batteries with ultra-capacitors for improved acceleration and energy storage, along with fuel cells, flywheels and regenerative braking. The propulsion system, combining electric, mechanical, chemical and electronics engineering, is a key challenge affecting vehicle design and performance. Additionally, the study develops an automatic solar power system with maximum power point tracking (MPPT) to optimise solar energy generation by considering sunrise and sunset times, panel size, charging duration, load profiling and power loss. The solar-based HEV, with an average speed of 60 km/h, can operate for 3.4 h or 204 km solely on solar power. Findings indicate a significant reduction in [Formula: see text] emissions, with solar HEVs emitting approximately 17,775,012.2 g and 13,825,009.5 g less [Formula: see text] than petrol and diesel vehicles, respectively. The study advocates for government adoption to promote a cleaner, more sustainable transportation sector in Bangladesh.